2015
DOI: 10.1108/ijcoma-12-2013-0132
|View full text |Cite
|
Sign up to set email alerts
|

What motivates Indian firms to invest abroad?

Abstract: Purpose -The purpose of this paper is to examine the motivations behind Indian firms' outward investment, i.e. whether these firms are investing abroad in search of market, resource, technology, strategic-assets, efficiency, etc. Outward FDI by Indian firms has increased considerably in recent years. Such investments have gone to more than hundred host countries and into various sectors. The higher volume of outward FDI following policy reforms requires examination of factors that have motivated Indian firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 53 publications
(90 reference statements)
2
37
1
Order By: Relevance
“…Supported by previous studies (e.g., Chen & Moore, 2010), gross domestic product (GDP) of hosts is taken as a proxy to represent market access. In the absence of data on wage of labourer, gross domestic per capita income (GDPPC) is taken as the proxy of labour cost which is supported by prior works (e.g., Das & Banik, 2015). Bellak, Leibrecht, and Riedl (2008) also observed that GDPPC and labour cost move in the same direction.…”
Section: Datamentioning
confidence: 93%
See 3 more Smart Citations
“…Supported by previous studies (e.g., Chen & Moore, 2010), gross domestic product (GDP) of hosts is taken as a proxy to represent market access. In the absence of data on wage of labourer, gross domestic per capita income (GDPPC) is taken as the proxy of labour cost which is supported by prior works (e.g., Das & Banik, 2015). Bellak, Leibrecht, and Riedl (2008) also observed that GDPPC and labour cost move in the same direction.…”
Section: Datamentioning
confidence: 93%
“…Therefore, it can be assumed that location distribution of OFDI is influenced by labour cost, capital cost, transaction cost, market access of the host country and total productivity of firms. Apart from these, signing of double taxation treaties (Das & Banik, 2015;Pradhan, 2011), openness of FDI sector (e.g., Ramasamy et al, 2012), availability of strategic assets and natural resources of host country (e.g., De Beule & Duanmu, 2012) also influence location choice of multinationals. Recently, growing intensity of Indian multinationals to invest in offshore financial centres (OFCs), such as Singapore, Mauritius and so on, has been observed.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This variable was found in the Heritage Foundation database. GDP per capita was used as a control variable because this dimension is often present in studies on institutional environment, as it represents the economic power of the population by the multinationals (Berry et al, ; Das & Banik, ) and franchise chains (Baena, ; Hoffman et al, ).…”
Section: Methodsmentioning
confidence: 99%